1996
DOI: 10.1128/aac.40.3.784
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of postantibiotic effect during one dosing interval of tobramycin, simulated in an in vitro pharmacokinetic model

Abstract: The kinetics of the postantibiotic effect (PAE) during one dosing interval of tobramycin against Staphylococcus aureus and Pseudomonas aeruginosa was investigated. We determined the PAE at different time points during this dosing interval of 12 h in an in vitro pharmacokinetic model simulating human pharmacokinetics in which the half-life of tobramycin was adjusted to 2.4 +/- 0.2 h. Using an enzymatic method to inactivate tobramycin, we determined PAEs in samples extracted from the model at 1, 5, 8, and 12 h, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Recently, we showed that the PAE completely disappeared during one interval of dosing with tobramycin simulated in an in vitro pharmacokinetic model (5). The PAE determined at the peak concentration (20ϫ the MIC) correlated well with the PAE measured under standard conditions, but it declined to zero at the end of a dosing interval.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Recently, we showed that the PAE completely disappeared during one interval of dosing with tobramycin simulated in an in vitro pharmacokinetic model (5). The PAE determined at the peak concentration (20ϫ the MIC) correlated well with the PAE measured under standard conditions, but it declined to zero at the end of a dosing interval.…”
mentioning
confidence: 67%
“…Another explanation might be a growth retardation due to free tobramycin which remains inside the bacteria and which is not removed during the washout phase of the PAE experiment. On the other hand, the disappearance of the PAE, which was observed during one interval of dosing with tobramycin (5), may be a result of the outgrowth of resistant subpopulations of bacteria. Alternatively, the phenomenon may be due to slow diffusion of tobramycin out of the bacteria or may be a result of a fast repair process in the bacteria.…”
mentioning
confidence: 99%
“…The pharmacokinetics of aminoglycosides in patients with CF has been evaluated extensively [33][34][35][36][37][38][39][40][41][42][43][44]. The volume of distribution per kg body weight is often increased, and the elimination half-life is decreased [40].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…An adjustment of dosing to achieve high serum levels has a significant effect on pulmonary function [39]. If aminoglycosides are given at higher doses, the dosing frequency may be reduced due to the sub-inhibitory MIC effect, the bactericidal concentration-dependent killing and adaptive resistance [41]. Indeed, high aminoglycoside doses given at once-daily intervals have been shown to be less toxic and equally effective when data from four studies comparing once-and three-times-daily aminoglycoside regimens were analysed [37].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In vitro data suggests that the PAE decreases with decreasing tobramycin concentrations during a 12hour dosing interval. 39 The optimal empiric dosage of SDD aminoglycoside therapy (3 to 7 mg/kg/day) is also controversial. If SDD aminoglycoside regimens are used, serum concentration monitoring should be used to tailor therapy, especially for patients with fluctuating pharmacokinetic parameters or renal function.…”
Section: Single Daily Dose Aminoglycoside Regimensmentioning
confidence: 99%